Filling gaps between museum and society: An illustrated catalog of the primary type specimens of Squamata housed in the Museu Nacional, Rio de Janeiro, Brazil - Passos, Paulo; Rodrigues, Rafael; Pinna, Pedro H.; Woitovicz-Cardoso, Manoela; Fernandes, Ronaldo; Caramaschi, Ulisses (Zootaxa, 2025)
Scientific collections constitute an impressive record of life on Earth and therefore play a key role for documentation of the historical spatiotemporal patterns of changes in biodiversity. The Museu Nacional/UFRJ in Rio de Janeiro, Brazil, houses collections dating back to the to the mid-19th Century. In order to maximize preservation and management of the Museu Nacional’s herpetological collections, the digitization process began with priority given to the primary type specimens. We provide an illustrated catalog based on right-resolution 2D images with purpose to make the collection of primary type specimens of Squamata housed at the Museu Nacional more accessible, facilitating taxonomic research and scientific dissemination to society. A total of 63 primary types (55 holotypes, 5 syntypes, 2 lectotypes, and 1 neotype) were photographed; these species are allocated in 16 families and 34 genera, geographically concentrated in Brazil. In addition, the Museu Nacional/UFRJ houses another 702 secondary types of reptiles (all paratypes) classified in 16 families and 37 genera, geographically concentrated in South America, including two Testudines species. We discussed the relevance of collections housed in natural history museums, highlighting that they represent essential tools for both short-term and long-term studies on biodiversity, including species that are already extinct in the nature. In addition, we noted that digitization process of preserved specimens and their metadata allow broader remote access information and, as an indirect consequence, it helps to preserve the physical specimens by reducing the need of direct handling, increasing the longevity of the samples for the future generations.